Pelepasan Hak atas Tanah bagi Pembangunan untuk Kepentingan Umum PT. Bali Pecatu Graha (Studi Kasus Kerkara Nomor: 65k/pdt/2012/ma) - Wayan Artana; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Warmadewa Press, 2021)
Currently, land conflicts that occur are generally caused by conflicts of interest with applicable laws and regulations and often inappropriate compensation. This study aimed to examine the legal arrangements for relinquishing land rights for development in the public interest in Indonesia which refers to Law Number 2 of 2012 and uncover legal protections for relinquishing land rights for development in the public interest of PT. Bali Pecatu Graha. The research method used was descriptive-analytical with a normative juridical approach and qualitative juridical analysis. The data used were primary and secondary legal data obtained through card system techniques. The results of the study indicated that the release of the land refers to Law no. 2 of 2012 and Law no. 5 of 1960. Legal protection for PT. Bali Pecatu Graha due to the act of relinquishing land rights must obtain legal certainty of relinquishment of land rights and requires the availability of written, complete and clear legal instruments that are carried out consistently in accordance with the spirit and content of the provisions so that personal interests get optimal legal protection